Synthesis of Optically Active Hydroxyalkyl Cycloheptatrienes: A Key Step in the Total Synthesis of 6,11-Methylene-LXB4 - Nava, Analuisa; Trippe, Lukas; Frank, Andrea; Andernach, Lars; Opatz, Till; Nubbemeyer, Udo (Synlett, 2020)
Starting from methyl cycloheptatrienyl-1-carboxylate, 6-acylation was successfully achieved employing glutaryl chloride in the presence of AlCl3 under controlled reaction conditions to furnish keto carboxylic acid product. After protection of this keto carboxylic acid as tert-butyl ester, reagent-controlled enantioselective reductions delivered configuration-defined methyl-6-hydroxylalkyl cycloheptatriene-1-carboxylates with up to 80% ee. Whereas simple NaBH4 reduction of the keto carboxylic acid and subsequent lactonization afforded a methyl-6-tetrahydropyranonyl cycloheptatriene-1-carboxylate. Resolution using chiral HPLC delivered the product enantiomers with up to >99% ee Finally, ECD analyses enabled structure elucidation. The products are used as key intermediates in enantioselective 6,11-methylene-lipoxin B4 syntheses.
Keywords: lipoxin analogue; cycloheptatriene; electrophilic acylation; enantioselective reduction; chiral HPLC; ECD analysis